Measuring Pro-poorness: A Unifying Approach with New Results - Essama-Nssah, B. (2012)
Recent economic literature on pro-poor growth measurement is drawn together, using a common analytical framework which lends itself to some significant extensions. First, a new class of pro-poorness measures is defined, to complement existing classes, with similarities and differences which are fully discussed. Second, all of these measures of pro-poorness can be decomposed across income sources or components of consumption expenditure (depending on the application). This permits the analyst to "unbundle" a pattern of growth, revealing the contributions to overall pro-poorness of constituent parts. Third, all of these pro-poorness measures can be modified to measure pro-poorness at percentiles. An application to consumption expenditures in Indonesia in the 1990s reveals that the poverty reduction achieved remains far below what would have been achieved under distributional neutrality. This can be tracked back to changes in expenditure components.